Analysis of Effectiveness Argument-Driven Inquiry to Improve Students’ Argumentation Skill and Conceptual Understanding - Agustina Dua Kuki; Rudiana Agustini; Utiya Azizah (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: This study examined the effectiveness of the Argument-Driven Inquiry learning model in science learning in improving students' argumentation skills and conceptual understanding. Method: The techniques used are 1) searching articles on Scopus and Google Scholar using the keyword Argument-Driven Inquiry in science learning, 2) articles were selected focus on increasing conceptual understanding and argumentation skills, 3) the metadata was selected limited to 2015-2023, and 4) conducting the in-depth review. Results: The ADI model was able to improve students' argumentation skills. In general, students' argumentation levels are in levels 3-4. The quality of the arguments developed by students shows the understanding of the concepts possessed by students. Students can reach the cognitive level created (C6) by writing scientific reports. Novelty: This study reinforces previous research regarding the effectiveness of the ADI model in improving argumentation skills and conceptual understanding taken from recent articles. Therefore, this article can be the basis for developing learning tools for the ADI model.